Perubahan Sosial Tradisi Hari Obor Pattimura Di Negeri Tuhaha Dan Siri-sori Amalatu, Kecamatan Saparua Timur, Kabupaten Maluku Tengah (Dalam Periode 2020-2022) - Wailissa, Ari Fisal; Watloly, Aholiab; Matakena, Fransina (Jurusan Sosiologi FISIP Universitas Pattimura, 2023)
Social changes in the Pattimura torch day tradition have been going on since 1979. The changes that occurred were caused by the conflict between the people of Tuhaha and Siri-sori Amalatu Village, which occurred in 1978. It does not stop there the conflict that occurred in 1999 in Ambon, the conflict between Batu Mera and Soya in 2012 the government in this case took over to change the form of the tradition so that it brought considerable influence. In 2020, due to the COVID-19 pandemic, a decision from the Government and Kings throughout Saparua, in 2020 the Pattimura torch day tradition was not carried out. In 2021 and 2022, Pattimura's torch day has changed to the location of the torch fire custom, the location of the torch fire cultivation channel, the location of the torch fire burning, and the role of the people of Siri-sori Amalatu Village as traditional children in the Pattimura torch day tradition. Which is caused by covid, conflict, diffusion/spread of new understandings, and the will of the Government. As a result of this change in this tradition, the values contained in the tradition began to deteriorate which had a negative impact on the social relations of the people of Tuhaha and Siri-sori Amalatu Village. Keywords: Tradition, Change, Social, Impact.